The impact of expressive elements in guiding the meanings of interactive texts – a pragmatic study - Mouazzouz, Abdelhalim (El Omda in Linguistics and Discourse Analysis, 2025)
This age is known as an unprecedented development in linguistic usage thanks to the development of means of communication among individuals, especially among young people who were able to modernize technologies in a remarkable manner, so that this group of society has created for itself a unique and non-traditional communication system based mainly on non-rhetorical elements To express elements, most of them overly cut, such as tones and forms of speech. These rhetorical elements would make speeches, which take a form of writing, and which were previously indirect speeches, more effective. This research looks at these expressive forms and reveals the deliberative dimensions of this contemporary expressionism among young people. It tries to categorize the discourse that uses the technique in contemporary linguistic discourse through different interactive models.